Infl uence of protein malnutrition on cutaneous wound healing in rats - Santos SAMPAIO, Laura Amélia; Santos COSTA, Jéssica; Fortuna Costa FREIRE, Tila; de Almeida REIS, Sílvia Regina; Bomfi m de Jesus DEIRÓ, Tereza Cristina; Ribeiro Alves Peixoto MEDRADO, Alena (Revista de Nutrição, 2023)
Objective Investigate histological changes related to infl ammatory response and collagen expression during wound healing in rats with protein malnutrition. Methods Twenty male Wistar rats underwent cutaneous surgery and were divided into two experimental groups: Malnourished (8% casein diet); Nourished (17% casein diet). Animals were euthanized after 5th and 10th days, descriptive and quantitative analyses were performed on sections stained with hematoxylin-eosin and sirius red, respectively. Statistical analysis of data using nonparametric Fisher's exact test with p<0.05 was carried out. Results At fi ve days, increased fi broblast proliferation (p<0.01) and collagen expression (p<0.05) was observed in N5 group. After ten days, N10 and MN10 animals showed higher amount of granulation tissue and edema/infl ammatory infi ltrate independent of nutritional status (p>0.05), only N10 group showed fi broblast proliferation (p<0.01) and increased collagen expression (p<0.01). Conclusion Protein malnutrition seems not to influence inflammatory phase of healing, whereas it negatively effects fibroblast proliferation and collagen synthesis.